معوقات الاستثمار السياحي في الجزائر وطرق تقويمه - زابي ىنيدة انتصار (جامعة المسيلة, 2021)
ملخص الدراسة أولا: العربية لقد سعت الحكومة الجزائرية إلى وضع إستراتيجية جديدة للسياحة الجزائرية تمتد إلى غاية 2025، عن طريق المخطط التوجيهي للتهيئة السياحية، والذي يعكس الإرادة السياسية في تطوير القطاع السياحي والنهوض به وجعله بديلا لقطاع المحروقات مستقبلا. ولهذا عمدت الدولة إلى توفير بيئة مشجعة للاستثمار السياحي، كسن القوانين و منح التحفيزات الجبائية وتقديم تسهيلات بخصوص العقار السياحي، غير أنه مازالت هناك مجموعة من المعوقات التي تعترض الاستثمار السياحي كتلك المرتبطة بالمحيط العام، كعدم توفير الاستقرار السياسي والأمني وعدم توفر بيئة اقتصادية مستقرة، صعوبة الحصول على العقار السياح، وصعوبة الحصول على التمويل البنكي. و عليه فإن تحسين مناخ الاستثمار يرتبط أيضا بتوفير جميع الظروف المحفزة للمستثمرين من إدارة نزيهة غير بيروقراطية، جهاز مصرفي متطور، محاربة الفساد، وإطار تنظيمي وتشريعي مناسب للاستثمار السياحي، يحفز المستثمر الأجنبي ويكون قادر على إقناعه بجدوى الاستثمار فيها. Study summary : The Algerian government has developed a new tourism strategy ranging from at the end of 2025, speaks of the master plan for the promotion of tourism, and which expresses the political will to develop the tourism and promotion sector and to make an alternative to the hydrocarbon sector in the future. That's why the state to ensure a favorable environment for investment including the allocation of tax incentives, financial facilities and supply in relation to the tourism building. But there are still a series of barriers to investment in the tourism sector, especially those related to the general environment, such as failing to ensure political stability and security and the absence of a stable economic environment and those tourism sector the difficulty of the tourism building and the difficulty of obtaining bank financing. Therefore, the improvement of the investment climate is linked and depends on all favorable investor circumstances such as an impartial and non-bureaucratic management, a banking system developed with such projects, and the fight against corruption and a regulatory framework. and appropriate legislation for investment of the tourism sector, which favors the foreign investor and be able to persuade him the usefulness of the investments .
Keywords: الاستثمار -السياحي -معوقات -طرق تقويمه